2009
DOI: 10.2340/16501977-0367
|View full text |Cite
|
Sign up to set email alerts
|

The practice of physical and rehabilitation medicine in sub-Saharan Africa and Antarctica: A white paper or a black mark?

Abstract: Antarctica is doing fine, but Africa is in a crisis. Local medical schools, hospitals doctors, and people with disabilities, along with foreign volunteers, aid groups, and policymakers can have an impact on the crisis. However, governments, specifically national ministries of health, are ultimately responsible for the health and well-being of their citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 3 publications
3
18
0
Order By: Relevance
“…52 km north-east of Kilifi is Malindi and 60 km south is Mombasa. Nevertheless, the gap between actual coverage and projected need would seem to be consistent with the findings from past research [2–5]. …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…52 km north-east of Kilifi is Malindi and 60 km south is Mombasa. Nevertheless, the gap between actual coverage and projected need would seem to be consistent with the findings from past research [2–5]. …”
Section: Discussionsupporting
confidence: 86%
“…More recently, reports of health-based rehabilitation services have revealed serious limitations in coverage and capacity [2–5]. When rehabilitation services do exist, they tend to be clustered around urban-based institutions [5,6] and are inadequately scoped to meet the needs of all service users [2]. Non-governmental organisations have arisen, usually to cater for specific areas of need that have been neglected [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of host rehabilitation and health services infrastructure compounds the lack of rehabilitation perspective; often few or no rehabilitation services or professional providers, especially PRM physicians, exist in areas affected by natural disasters (10, 4850). To compensate for this lack of expertise, rehabilitation training strategies are required (50, 51). Foreign rehabilitation responders can provide focused training to fellow team members as well as to local rehabilitation and non-rehabilitation providers in the field, hospital, and community settings throughout the disaster response.…”
Section: Impact Of Natural Disasters On Health and Rehabilitation Sysmentioning
confidence: 99%
“…This is partly related to lack of common definitions and classifications, partly to poor availability and use of standard statistical sources for workforce monitoring, and partly to lack of political will to place monitoring of human resources for rehabilitation high on the health agenda - the latter itself may be related to the way societies often interpret and react to disability. For instance, Haig et al facetiously concluded, taking into account the lack of documentation on physical and rehabilitation medicine in sub-Saharan Africa, the chance of a person with a disability in sub-Saharan Africa meeting a physician with specialist skills is about the same as that for an Antarctic penguin [14]. …”
Section: Introductionmentioning
confidence: 99%